Two cases of clump formation after thawing of hematopoietic progenitor cell products for transplantation - Gamba, Cecilia; Silvestri , María del Rosario; Miguel, Agustina; Labonia, Danila; Fernández Escobar, Nicolás; Pizzi , Silvia Mariana; Díaz Sánchez , Daniel; Staciuk, Raquel; Kuperman, Silvina Laura (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
While rare, clump formation has been described in the thawing of cryopreserved hematopoietic progenitor cell products intended for transplantation. When this occurs, it presents a significant challenge to the transplant team, potentially influencing the viability and safety of the product. Though the exact cause of clumping in thawed products remains unknown, studies have linked clump formation with the occurrence of adverse events. This report aimed to describe two cases of clump formation in thawed apheresis products observed in our processing laboratory, detailing the procedures followed and the outcomes achieved.